PENGARUH PENDEKATAN CONTEXTUAL TEACHING AND LEARNING TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIS PESERTA DIDIK KELAS VII SMP NEGERI 25 PADANG - Hayati, Sisri (Departemen Matematika, 2023)
Due to the insufficient problem-solving skills of VII pupils, this study was conducted. To counteract this, research was conducted to enhance students' problem-solving abilities through the Contextual Teaching and Learning (CTL) approach. The purpose of the study is to determine and describe the mathematical problem-solving ability of seventh-grade students at SMP Negeri 25 Padang whose learning with the CTL approach is superior to their mathematical problem-solving ability with the traditional learning model. And to understand and describe the development of mathematical problem-solving skills in students using the CTL method. This investigation utilised a quasi-experimental design. The design employed is a